COVID-19: A Daily Dose of Yoga to Cope with Anxiety - Gautam, Surabhi; Dada, Rima (Coronaviruses, 2021)
The coronavirus disease (COVID-19) pandemic has undoubtedly created unbearable psychological pressure on our minds such as anxiety, fear, worry, changing sleep patterns, changing eating patterns, worsening of existing chronic or mental health conditions, etc. There is an urgent need for the adoption of an effective coping strategy. We propose that yoga-based intervention may aid in improving mental and physical health with its multi-faceted dimensions.
Keywords: stress